Have exchange-listed firms become less important for the economy? - Schlingemann, Frederik P.; Stulz, René M. (Journal of Financial Economics, 2022)
Publicly traded firms contribute less to total nonfarm employment and GDP now than in the 1970s. Major reasons for this development are the decline of manufacturing, the shift towards more production abroad in manufacturing, and the growth of the service economy as firms providing services are less likely to be listed on exchanges. A firm's stock market capitalization is much less instructive about its employment now than earlier. Market capitalizations have not become systematically less informative about firms’ contribution to GDP. Listed stock market superstars account for less employment than they did in the 1970s.